1997
DOI: 10.1002/(sici)1097-0142(19970801)80:3<357::aid-cncr2>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated carcinoma of the major salivary glands

Abstract: BACKGROUND Undifferentiated carcinoma of the salivary glands is a rare disease, the incidence of which is highest among the Inuit of Greenland and North America. It was demonstrated to be closely related to Epstein‐ Barr virus (EBV) infection. However, the relation of EBV to this tumor has not been studied to any great extent here in Taiwan because of the small number of cases. METHODS Twelve cases of undifferentiated carcinoma of the salivary glands from the period 1977‐1996 were retrieved from the cancer reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…4 It seems there is a complex interaction between genetic factors, environmental factors, and EBV infection in the oncogenic process of LEC of the salivary glands. 9 Parotid LEC usually presents as an enlarging parotid lump, occasionally painful and with facial nerve involvement in approximately 20% of cases. 4 Clinical features suggestive of malignancy are rapid-growing course, pain or tenderness, progressive facial nerve palsy and obvious cervical lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 It seems there is a complex interaction between genetic factors, environmental factors, and EBV infection in the oncogenic process of LEC of the salivary glands. 9 Parotid LEC usually presents as an enlarging parotid lump, occasionally painful and with facial nerve involvement in approximately 20% of cases. 4 Clinical features suggestive of malignancy are rapid-growing course, pain or tenderness, progressive facial nerve palsy and obvious cervical lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced disease, the presence of metastases on diagnosis, and histological features such as high mitotic rate, anaplasia, and necrosis are predictors of a worse prognosis. 1,9 The 5-year survival rate has been reported to range from 50–87%. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Wahlberg et al reported 48% (95% CI = 40%–56%) 5‐year overall survival for a series of large and small cell undifferentiated carcinomas of the parotid containing 276 patients . One case series from Taiwan, where LEC is endemic, reports much more favorable 5‐year survival of 79.8% . Interestingly, Wang et al, in one of the few cases series separating LEC and LCUC, report survival rates of 85.6% (5 year) and 36% (2 year), respectively .…”
Section: Discussionmentioning
confidence: 99%
“… Large‐cell undifferentiated carcinoma seems to have relatively poor prognosis, is not associated with Epstein‐Barr virus (EBV), and does not seem to have a strong geographic predilection. In contrast, LEC is endemic to southern costal China, Taiwan, and Greenland, and is associated with EBV genomic integration . Outside of these endemic regions, the majority of undifferentiated salivary gland carcinoma is LCUC …”
Section: Introductionmentioning
confidence: 99%
“…Published studies may overestimate the prevalence of EBV infection in these tumors, because some investigators may only have reported EBV positive cases. In addition, the majority of the studies were small and examined the expression of only a restricted set of two viral genes that encode non-translated small RNAs (EBER-1 and EBER-2) using in situ hybridization 10, 26-31, 36-43. Fewer studies evaluated the expression of additional viral latency associated genes, although both latency patterns I (seen also in Burkitt lymphoma) and II (seen in Hodgkin lymphoma and nasopharyngeal carcinoma) have been detected in salivary gland lymphoepithelial carcinomas 9, 32, 33, 41, 44-49…”
Section: Discussionmentioning
confidence: 99%